A new species of Xenophrys (Amphibia: Anura: Megophryidae) from Truong Son Range, Vietnam - Luong, Anh Mai; van Hoang, Chung; Pham, Cuong The; Nguyen, Tao Thien; Orlov, Nikolai; Ziegler, Thomas; Nguyen, Truong Quang (Zootaxa, 2022)
A new species of Xenophrys is described from Truong Son Range in Central Vietnam based on morphological and molecular differences. The new species is distinguishable from its congeners by a combination of the following characters: Size medium (SVL 58.8–71.4 mm in males, 65.6–87.3 mm in females); tympanum distinct; vomerine teeth present; tongue notched posteriorly; external vocal sac absent; toes with rudimentary webbing; subarticular tubercles absent, lateral fringes narrow along toes; nuptial pads absent in males; dorsal skin of body with weak granules; flank with small tubercles; dorsum with a dorsal ridge in >-< shape; dorsolateral folds prominent; dorsal surface from reddish brown to grayish brown with a brown triangle between the eyes, and a dark brown marking edged along dorsal ridge on the back; and small white spots present on flank and back of thigh. In the phylogenetic analyses, the new species is nested within the genus Xenophrys with interspecific uncorrected genetic p-distances (16S rRNA gene) from 2.2–2.8% (compared with Xenophrys maosonensis) to 14.4–14.7% (compared with Xenophrys yeae).